2003
DOI: 10.1210/en.2003-0592
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Regulated Expression of Egr-1 and Krox20: Dependence on ERK1/2 and Interaction with p38 and PI3-Kinase Pathways

Abstract: In addition to its ability to rapidly alter metabolism, insulin is also able to regulate the expression of numerous genes via activation of the PI3-kinase (PI3-K), MAPK kinase (MEK)-ERK, or p38 pathways. Using differential screening of H4IIE cells, we have identified two members of the Egr zinc-finger transcription factor family of early response genes, Egr-1 and Krox20, whose transcription is induced by insulin treatment. Egr-1 may be involved in insulin's regulation of hepatic gene expression. Krox20 regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
65
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 73 publications
13
65
0
Order By: Relevance
“…In our experiments, the rapid and transient induction of EGR1 protein in response to exendin-4 ( Fig. 8a) was consistent with previous studies [9,34]. In addition, the time course of EGR1 protein induction was consistent with that of EGR1 binding to the radiolabelled oligo 5′ probe (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our experiments, the rapid and transient induction of EGR1 protein in response to exendin-4 ( Fig. 8a) was consistent with previous studies [9,34]. In addition, the time course of EGR1 protein induction was consistent with that of EGR1 binding to the radiolabelled oligo 5′ probe (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Expression of Egr1 is rapidly induced by mitogens, insulin and glucose in different cells, including beta cells [19,20,34,35]. In our experiments, the rapid and transient induction of EGR1 protein in response to exendin-4 ( Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Consistent with its role as an immediate early gene, Egr-1 mRNA levels rise and peak early after stimulation with insulin then decline quickly, with a corresponding pattern of protein expression (Figure 1). This time course of insulin induced increase in Egr-1 mRNA levels has been observed in many tissues (Barroso and Santisteban, 1999;Tan et al, 2003;Silverman and Collins, 1999;Leung-Theung-Long et al, 2005;Garnett et al, 2005) as has its dependence on the MAP kinase pathway (Leung-Theung-Long et al, 2005;Garnett et al, 2005;Keeton et al, 2003). The GnRH mRNA level peak after one hour of insulin treatment corresponds with the time of maximal Egr-1 protein levels, suggesting that higher protein levels, rather than protein activation, promote binding of Egr-1 to the GnRH promoter.…”
Section: Discussionmentioning
confidence: 62%
“…We previously demonstrated that insulin exerts its effect on GnRH promoter activity via a MAP kinase pathway (Kim et al, 2005); in other cell systems, insulin mediated induction of Egr-1 is dependent upon activation of the Ras/Raf/MAP kinase pathway (Keeton et al, 2003). In order to investigate whether the effect of insulin on Egr-1 is mediated by the MAP kinase pathway in the GN11 cells, cells were pre-treated with PD98059--a specific inhibitor of MEK, the upstream regulator of MAP kinase-then treated with insulin.…”
Section: Insulin Induction Of Egr-1 Requires Activation Of a Map Kinamentioning
confidence: 99%
See 1 more Smart Citation